2022
DOI: 10.3390/ijerph192215203
|View full text |Cite
|
Sign up to set email alerts
|

New Dimension on Quality of Life Differences among Older Adults: A Comparative Analysis of Digital Consumption in Urban and Rural Areas of China

Abstract: The purpose of this study was to compare the variability in quality of life in the area of digital consumption among older adults in urban and rural China during the COVID-19 pandemic. This study proposed a low-cost mixed research method, and the methodology used a quantitative study of a large regional sample combined with a qualitative study of a small regional sample. Data for the large-scale area sample were obtained from the China family panel study (CFPS) dataset, and data for the small-scale regional sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
1
1
Order By: Relevance
“…No significant differences were found regarding place of residence, except among women, for whom living in a rural area had a protective effect on the evolution of QoL compared to living in a large city. These results differ from those of previous research, such as that of Lenehan et al [ 38 ] in 2020, in which their meta-analysis showed that older adults living in rural areas had significantly lower health-related QoL than those living in urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…No significant differences were found regarding place of residence, except among women, for whom living in a rural area had a protective effect on the evolution of QoL compared to living in a large city. These results differ from those of previous research, such as that of Lenehan et al [ 38 ] in 2020, in which their meta-analysis showed that older adults living in rural areas had significantly lower health-related QoL than those living in urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Especially for patients living in remote and rural areas in China, geographical constraints severely affect the HRQOL of patients and caregivers due to the lack of timely psychological support. 30 The implementation of ACT intervention also encountered challenges in the COVID-19 situation from our research team, such as face-to-face conduct mode. 31 Alternatively, increasingly digital-based ACT interventions have been developed and shown considerable effects for different populations.…”
Section: Introductionmentioning
confidence: 99%